Analysis of Factors Related to Stunting Incidence in the Service Area of Alak Health Center, Kupang City - Picauly, Intje; Pello, Feno Adrianus (Pergizi Pangan DPD NTT, 2025)
Background: Stunting is a condition in a person who has a length or height that is lacking. The main factors that cause stunting are family knowledge of nutrition, sanitation and family support. Objectives: This study aims to determine the Relationship between Income, Exclusive Breastfeeding History and Nutritional Intake with Stunting Incidents in the Alak Health Center Work Area. Methods: The type of research used is an analytical survey with a cross-sectional study approach. The number of samples in this study were toddlers aged 1-3 years who were taken using a simple random sampling technique. Sampling used a lottery technique. Each variable studied was tested using the Chi-Square test to determine the relationship between the variables of Income, Exclusive Breastfeeding History in Nutritional Intake. To test the significance, the researcher used a p-value with a significance level of 5% and a confidence level of 95%. Results: Monthly food (pVal : 0.005) and non-food expenditure (pVal : 0.003), history of exclusive breastfeeding (pVal : 0.004) and nutritional intake (pVal : 0.003 – 0.005) are related to the incidence of stunting, while monthly income is not related to the incidence of stunting in the Alak Health Center work area. Conclusions: The amount spent on food and non-food needs per month along with factors of exclusive breastfeeding history and nutritional intake are related to the incidence of stunting. Other factors such as the amount of income per month are not related to the incidence of stunting in the Alak Health Center work area.